DETERMINAN PENGANGGURAN GENDER PADA NEGARA LOWER MIDDLE INCOME DI ASEAN - Yulia Ulan Sari; Hasdi Aimon (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
The study explained the effect of the amount of people age 15-64 years, the labor and the dependency ratio toward the gender unemployment ratio. The method that is used in the reasearch is the panel regression model. This data used a combination method between time series data from 2000 – 2017 and cross section data obtained from the World Bank annual report. The results of this study show that the ratio of the number of residents aged 15-64 years has no significant positive effect on the gender unemployment ratio, the ratio of labor has a significant negative effect on the gender unemployment ratio, and the dependency ratio has a significant positive effect on the gender unemployment ratio.